Evaluating Organizational Performance of Public Hospitals using the McKinsey 7-S Framework - Malgorzata Chmielewska; Jakub Stokwiszewski; Justyna Markowska; Tomasz Hermanowski (BMC, 2022)
Abstract Background This study examined non-financial aspects of the organizational performance of public hospitals from the perspective of hospital physicians; the obtained results were analyzed to identify the necessary improvements in organizational performance. Methods This was a cross-sectional study of multidisciplinary public hospitals on a group of 249 randomly selected physicians from 22 in-patient departments or clinics operating in the Warsaw region. The study data was collected using the structured World Health Organization questionnaires (to be filled out by respondents) assessing the hospital's organizational performance variables qualified according to the McKinsey 7-S Framework. Epidata software version 3.1 was used for data entry, and the analysis was carried out in the SPSS software, version 19. The results of the organization evaluation are presented in the McKinsey 7-S Framework diagram. Key elements of the performance factors were grouped into 'stens', and the sten values were expressed as arithmetic means. Normal distribution of the stens was validated with the Kolmogorov-Smirnov test. 95% confidence intervals were calculated. The significance of differences between the analyzed stens was compared with the paired Student t-test. The interdependence of the variables was determined using the Pearson's correlation coefficient. Results The results revealed a significant difference (p <0.05) in the respondents' assessment of social (a mean score of 2.58) and technical (a mean score of 2.80) organizational aspects of the hospital operation. Scores for all variables were low. The social elements of an organization with the lowest score included 'staff', and in it the aspect - 'efforts are made to inspire employees at the lowest levels of the organization', 'skills' involving the learning style followed by the management/managerial staff, and 'management style' (average scores of 2.38, 2.56, 2.61, respectively). Conclusion Consistently with the existing literature, social factors were shown to play a more significant role in the management and they therefore deserve careful attention and more recognition when identifying and improving the key aspects affecting the organizational performance of public hospitals. Technical elements (strategy, structure, system) are important, but were demonstrated to have limited effect on the organizational operations geared towards ensuring effective functioning of a public hospital.